Two new species and additional records of the genus Asiageodromicus Shavrin, 2024 from Xizang, southwest China (Coleoptera, Staphylinidae, Omaliinae) - Yi Yang; Nima Danzeng; Zhong Peng (ZooKeys)
Asiageodromicus dawai Yang & Peng, sp. nov. (Xizang: Langkazi) and Asiageodromicus zhangi Yang & Peng, sp. nov. (Xizang: Cuona) are described and illustrated. Additional records of A. namucuoicus (Cheng & Peng, 2020) are reported. A key to the Chinese species of the genus Asiageodromicus Shavrin, 2024 is given.